1981
DOI: 10.1128/jb.148.1.341-351.1981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new developmental locus in Bacillus subtilis by construction of a deletion mutation in a cloned gene under sporulation control

Abstract: We removed by recombinant deoxyribonucleic acid (DNA) techniques a small DNA segment from within a cloned gene (the 0.4 kb gene) in which transcription in under sporulation control in Bacillus subtilis. These deletion mutation was introduced into the B. subtilis chromosome by transformation with cloned DNA. Competent cells bearing a mutation (tms-26) that is closely linked to the 0.4 kb gene were transformed with linearized plasmid DNA containing the truncated 0.4 kb gene and the wild-type allele of the tms lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 22 publications
(22 reference statements)
0
25
0
Order By: Relevance
“…Although the absence of spoVG causes little impairment in sporulation in the model organism B. subtilis, it caused aberrations in the cortex [7,16] and amplified the effects of a spoIIB mutation [5,15]. To investigate whether SpoVG influenced sporulation in B. anthracis A16R, a spoVG mutant (∆spoVG) and a plasmid-based complementation strain (R∆spoVG) were constructed.…”
Section: Deletion Of Spovg Results In a Spore Formation Defect In B mentioning
confidence: 99%
“…Although the absence of spoVG causes little impairment in sporulation in the model organism B. subtilis, it caused aberrations in the cortex [7,16] and amplified the effects of a spoIIB mutation [5,15]. To investigate whether SpoVG influenced sporulation in B. anthracis A16R, a spoVG mutant (∆spoVG) and a plasmid-based complementation strain (R∆spoVG) were constructed.…”
Section: Deletion Of Spovg Results In a Spore Formation Defect In B mentioning
confidence: 99%
“…Unfortunately, fragment 14 in pPL714 did not specify any additional detectable host phenotype. One approach to assigning a genetic function to fragment 14 involves introducing a deletion within the fragment into the B. subtilis chromosome and observing the phenotypic variation in the host cell (22). This has been tested by recombining a derivative of fragment 14, deleted for an internal 2-kb BclI-HpaI segment (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since H is active in a citC mutant (28), the mechanism by which the absence of ICDH activity interferes with asymmetric septation is not known. As shown in the accompanying paper (36), further analysis of the stage I block in a citC mutant has revealed that inactivation of the spoVG gene (42,44,46) allows the mutant cells to overcome in part their defect in asymmetric septation and activate forespore-specific, F -dependent genes. SpoVG, which is induced at the onset of stationary phase (54), acts as a transient negative regulator of the pathway leading to asymmetric septum formation (36).…”
mentioning
confidence: 98%